The effects of tryptophan depletion on cognitive and affective processing in healthy volunteers. - Murphy, F; Smith, K; Cowen, P; Robbins, T; Sahakian, B (2002)
RATIONALE: Cognitive impairment is a common feature of depressive illness. While accumulating evidence suggests that brain serotonin (5-HT) pathways play an important role in the neurobiology of depression, the extent to which altered 5-HT function is responsible for the associated changes in cognition and emotion remains unclear. OBJECTIVE: The present study examined the effects of acute dietary depletion of tryptophan (TRP) on cognitive and affective processing in healthy volunteers and explored the putative role of 5-HT in the neuropsychology of depression. METHODS: We administered computerised cognitive tests to healthy control participants following ingestion of TRP-free and nutritionally balanced amino acid drinks in a double-blind, placebo-controlled, crossover design. RESULTS: The TRP-free amino acid mixture significantly lowered plasma total and free TRP concentrations relative to baseline values and produced selective deficits similar to those observed previously in cases of clinical depression. In particular, TRP depletion increased response times for happy but not sad targets in an affective go/no-go task and slowed responding in a visual discrimination and reversal learning task. These deficits were not due to a global sedative effect, as planning ability was unimpaired. CONCLUSIONS: The present data indicate that serotonergic factors may be more involved in the disrupted inhibitory and emotional processing characteristic of depression than in other aspects of executive function, such as planning ability. These findings support the recent proposal that serotonergic manipulation may have greater effects on tasks mediated by frontal circuitry that includes the orbitofrontal cortex than by dorsolateral prefrontal cortex circuitry.